2015 IEEE World Haptics Conference (WHC) 2015
DOI: 10.1109/whc.2015.7177705
|View full text |Cite
|
Sign up to set email alerts
|

Wearable skin vibration sensor using a PVDF film

Abstract: This paper aims to develop a wearable tactile sensor for measuring skin vibrations using a polyvinylidene fluoride (PVDF) film, which is a polymer piezo material. The sensor is worn on the finger pad where is remote from contact fingertip and detects skin-propagated vibrations when fingertip touches an object. The proposed sensor allows users to touch with bare fingers and to conduct active touch. A transfer function from vibrations applied on the fingertip to the sensor output is expressed by using a finger m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(15 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Wearable Devices. In this study, the wearable skin vibration sensor developed by Tanaka et al [10] is used for sending tactile information from the human to the robot. The sensor uses polyvinylidene difluoride (PVDF) film and detects vibrations propagating on the human skin surface.…”
Section: Methodsmentioning
confidence: 99%
“…Wearable Devices. In this study, the wearable skin vibration sensor developed by Tanaka et al [10] is used for sending tactile information from the human to the robot. The sensor uses polyvinylidene difluoride (PVDF) film and detects vibrations propagating on the human skin surface.…”
Section: Methodsmentioning
confidence: 99%
“…Contact with any surface is associated with movement which is expected to lead to small vibrations of the finger. Previous studies have shown that these vibrations can be useful to detect roughness of touched materials [15,16].Using a stethoscope, Delhay et al have showed that vibrations generated as a result of interaction of a finger with a rough surface is transmitted even uptill the wrist [10]. We therefore hypothesized that an accelerometer mounted on a finger may serve as a suitable transducer to decode surface texture, and hence material.…”
Section: Introductionmentioning
confidence: 95%
“…Although wearable tactile sensors equipped with accelerometers can be light, cheap, and simple, they place strict constraints on the speed of exploration, because together with skin vibrations, the sensor output includes the motion of body parts. In the proposed study, we utilized the wearable skin vibration sensor developed by Tanaka et al [16], shown in Fig. 2.…”
Section: Wearable Vibration Sensormentioning
confidence: 99%